2002
DOI: 10.1139/y01-093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin A deficiency on cardiovascular function in the rat

Abstract: Selected parameters of cardiovascular function were evaluated in vitamin A-deficient rats at 70 days of age. Resting heart rate was increased by an average of 100 bpm (21.4+/-2.7%), whereas resting systolic blood pressure was normal in vitamin A-deficient animals. The maximal contractile force developed per milligram weight of tissue by aortic rings excised from vitamin A-deficient animals was reduced in response to high potassium (-25.0+/-8.7%) and phorbol 12,13-dibutyrate (-36.8+/-8.4%) but was only slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
2
5
1
Order By: Relevance
“…This is the first study to show an increase in relative heart weight in the offspring at birth from mothers with moderate vitamin A deficiency. This result would agree with the finding of increased relative heart weight with marginal vitamin A deficiency in rats at day 18 of life by Wright et al (34). However, a previous moderate vitamin A deficiency study (3) did not detect this increase; however, this latter study measured relative organ weights at 20 days gestation and not at birth.…”
Section: Verification Of the Moderate Vitamin A Model And Effects On supporting
confidence: 92%
“…This is the first study to show an increase in relative heart weight in the offspring at birth from mothers with moderate vitamin A deficiency. This result would agree with the finding of increased relative heart weight with marginal vitamin A deficiency in rats at day 18 of life by Wright et al (34). However, a previous moderate vitamin A deficiency study (3) did not detect this increase; however, this latter study measured relative organ weights at 20 days gestation and not at birth.…”
Section: Verification Of the Moderate Vitamin A Model And Effects On supporting
confidence: 92%
“…Retinoids may be useful in the management of hypertrophic/hyperproliferative disorders of the heart and vascular wall (Gardner, D. G., and Chen, S., 1999). In addition, vitamin A deficiency causes a significant decrease in contractile responsiveness of aortic smooth muscle as a result of a down-regulation in the expression of contractile-related proteins (Wright, G. L. et al ., 2002). Retinoids have also been shown to regulate cardiac mitochondrial membrane potential (Korichneva, I. et al ., 2003).…”
Section: Identification Of the Rbp Receptormentioning
confidence: 99%
“…Wright and co-workers [68] showed that the contractility of aortic SMCs could be restored in aortic rings when incubated with atRA [68]. A more recent report from the same group [67] showed a reduced contraction of aortic rings from vitamin-A-deficient rats. A study [69] from the group that identified KLF5 as a potential target for retinoid-induced inhibition of SMC proliferation showed that Am80, a synthetic RARα agonist, inhibits serum-induced down-regulation of smooth muscle α-actin and MHC both in vitro as well as in vivo.…”
Section: Vitamin a And Smc Differentiationmentioning
confidence: 96%
“…Endogenous RA signalling has been shown to co-localize with the expression of the adult smooth muscle MHC during development of the ductus arteriosus [66]. Furthermore, the level of α-actin has been shown to be reduced in SMCs from vitamin-A-deficient rats compared with controls [67]. One definition of fully differentiated SMCs is the ability of these cells to respond to contractile agonists.…”
Section: Vitamin a And Smc Differentiationmentioning
confidence: 99%